Investigating Role of IL-39, IL-37 and Some Biochemical Parameters in Patients with Acute Interstitial Nephritis - Sayer, Sarah A (Indonesian Journal on Health Science and Medicine, 2025)
Background: Acute interstitial nephritis causes blood flow to be impaired, this ultimately leads to inflammation and edema in the renal tubules and tissues, this decreases the glomerular filtration rate (GFR). Early detection and treatment of the disease can mitigate the progression of renal failure. To investigate the potential for IL-39 and IL-37 to be used in the diagnosis of acute interstitial nephritis, this study sought to measure the levels ofinflammatory markers, interstitial nephritis, and antioxidant agents in patients with acute interstitial nephritis using receiver operating characteristic (ROC) graphs.Methods: The investigation had 25 patients and 25 controls that were between the ages of 40 and 65 during the years 2023 and 2024.Results: The outcomes demonstrated that the concentrations of urea, creatinine, C-reactive protein (CRP), IL-39, IL-37, and MDA in the patient's blood were significantly greater than those in the control's. However, the concentrations of albumin, GSH, and SOD in the blood of the patients were significantly lower than those of the controls. Additionally, the ROC curve demonstrated that the concentrations of MDA,TNF-α,GSH,SOD,IL-39, and IL-37 were effective at differentiating patients with acute tubular necrosis from healthy individuals. Overall, inflammation has been linked to increased oxidative stress, the release of proinflammatory cytokines, and the development of an inflammation state. As a result, understanding the total disease burden and adding extra criteria will facilitate the early detection or preemptive risk assessment for each patient. This will facilitate future investigations of the pathophysiology of diseases in diagnosis, prognosis, and treatment. Highlight IL-39 and IL-37 show strong diagnostic potential for acute interstitial nephritis. Patients exhibited higher inflammation and oxidative stress markers, with reduced antioxidant levels. ROC analysis confirmed several biomarkers as effective differentiators from healthy controls. Keywords: Acute Interstitial Nephritis, IL-39, IL-37, Oxidative Stress, ROC Curve